Improving the accuracy of indoor user location using IEEE 802.11 signals - Mantoro, Teddy; Ayu, Media Anugerah (2010)
The best candidate to determine a user location in indoor environment is by using IEEE 802.11 (Wi-Fi) signals, since it is more and more widely available and installed on most mobile devices used by users. Unfortunately, the signal strength, signals quality and noise of Wi-Fi, in worst scenario, fluctuate up to 33% because of the reflection, refraction, temperature, humidity, the dynamic environment, etc. This makes problems in determining a user location indoor. This study presents our current development on a light-weight algorithm, which is designed to be easy, simple but robust in producing the determination of user location. We study user location accuracy and the error levels to verify the mislead determination of the user location and improve the accuracy of the user location based on multiple observers" ηk- Nearest Neighbor.